Personalisation: Direct Payments and Mental Illness - Dr , Christopher Alan Griffiths (International Journal of Psychosocial Rehabilitation, 2014)
Purpose: Since 2007 local authorities in the UK have been charged with implementing direct payments for people receiving social care. Direct payments allow people to make purchases to meet their needs. This study investigated the experiences of seeking to obtain and use direct payments of people who experience mental illness and their carers. Design/methodology/approach: A qualitative methodology using telephone semi-structured interviews to collect the data from 12 people with experience of mental illness and 9 carers was employed. Findings: Interviewees were motivated to seek direct payments to meet their needs not being met through current services. Knowledge- able and supportive carers and healthcare professionals were vital in helping many people who experience mental illness to achieve, manage and maintain direct payments. The process for direct payments can be complex, time consuming and stressful, requiring a high level of cognitive skills and assertiveness. Benefits of direct payments include: ability to improve social lives, reduce hospital admis- sions, raise standards of living, increase levels of empowerment, improve mental and physical health, and improve prospects for obtain- ing employment. Conclusion: In general interviewees felt that the benefits of direct payments outweighed the difficulties. There is a need to simplify and improve the processes involved in obtaining and maintaining direct payments. If the direct payments process becomes further refined, established and uncertainness removed, it may result in a higher take-up of direct payments for people who experience mental illness.